PELATIHAN MANAJEMEN PENJUALAN BERBASIS RELATIONSHIP - Rodhiah; Aritonang R., Lerbin Roberto (Transpublika Publisher, 2022)
The relationship between a business and its sales force is referred to as relationship management, which has a role in focusing on increasing sales for the long term. The relationship between sales management and labor relations management must be maintained properly, because the task of a sales management is to cultivate, train and select salespeople and become the key to successful sales of the products produced. Supporting a relationship-based sales management strategy will encourage the creation of a comfortable working atmosphere for salespeople, which will increase motivation in making sales. Activity partners are engaged in the damar handicraft business located in Serang Banten. In its activities, it faces problems, especially in terms of sales management strategies. PKM aims to assist partners in an effort to improve their ability to improve sales management strategies based on relationships with salespeople. The activity method is carried out by training related to sales management science. The training was conducted online. The results of the activity show that the provision of knowledge about relationship-based sales management is delivered in the form of PPT, the implementation of activities involving two students has been realized and is running smoothly. Partners gain knowledge in improving the role of salespeople to generate more sales.